Captive Breeding of the Shark Bay Mouse Pseudomys fieldi to Facilitate Species Recovery in the Wild - Lambert, Cathy; Power, Vicki; Gaikhorst, Glen (Journal of Zoo and Aquarium Research, 2016)
Shark Bay Mice (P. fieldi) were bred at Perth Zoo to provide animals for release to the wild as part of recovery actions for the species. Three-hundred and thirty-five young were produced from 93 litters, with an average litter size of 3.6 (range 1 – 6). Sexual maturity for both sexes was reached at 65 days of age, and breeding was observed all year round. The oldest female to give birth was 625 days of age and the oldest male to sire young was 531 days of age. Following a planned interruption to the program and the separation of breeding pairs, there was some difficulty in later re-establishing reproduction. A strategy to stimulate a return to breeding, along with detailed husbandry methods, is described.